ANALISIS SUDUT DISPERSI PADA PRISMA DENGAN INDEKS BIAS DAN KETEBALAN YANG BERBEDA - Syahril, Latifa Rahmi (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2024)
This research analyzed the angle of dispersion in prisms with different refractive indexes and thicknesses. The results showed that the angle of dispersion in thick prisms is greater than that in thin prisms. This is due to the fact that the refractive index of thick prisms is greater than that of thin prisms. In a prism, white light with different wavelengths is refracted at different angles. This difference in refraction angles is called the angle of dispersion. The refractive index of thick prisms is greater than that of thin prisms, so white light passing through thick prisms will experience greater refraction. This greater refraction will also result in a larger angle of dispersion. The findings of this study show that the refractive index and thickness of a prism have a significant effect on the angle of dispersion. A larger refractive index will result in a larger angle of dispersion, and a thicker prism will also result in a larger angle of dispersion. Keywords: prism, thickness, scattering angle,refraction index